Urine from Sexually Mature Intact Male Mice Contributes to Increased Cardiovascular Responses during Free-Roaming and Restrained Conditions. (9th February 2012) - Lee, Dexter L.; Wilson, Justin L.
Abstract : Pheromones in the urine regulate aggression of male mice and castrated males produce less of these pheromones. We tested the hypothesis that pheromones in the urine of sexually mature-intact (SMI) males placed in the cage bedding of an individually housed male mouse or in a mouse restrainer would contribute to a significant increase in mean arterial pressure (MAP), heart rate (HR), and activity. Sexually mature male C57BL/6 mice were implanted with a biotelemetry transmitter to measure MAP, HR, and activity. Urine (200 μL) from SMI mice placed in the cages of singularly housed male mice caused significant changes above baseline values for MAP (21 ± 4  mmHg), HR (145 ± 25  bpm), and activity (9 ± 2  counts) when compared to urine from castrated mice-induced MAP (11 ± 3  mmHg), HR (70 ± 15  bpm), and activity (5 ± 1  counts). Pretreatment with terazosin significantly reduced the change in MAP (9 ± 3  mmHg), heart rate (90 ± 15  bpm), and activity (4 ± 2  counts) responses to urine from SMI males. Saline did not significantly increase MAP, HR, or activity in any group. During restraint, urine from SMI mice caused a significant change in MAP (5 ± 0.4  mmHg) and HR (17 ± 1  bpm); urine from castrated mice did not cause a significant increase in MAP and HR. Our results demonstrate that a significant increase in MAP, HR, and activity occurs when male mice are exposed to urine pheromones from SMI males. In summary, pheromones in the urine of SMI male excreted in the cage bedding and mouse restrainers contribute to a significant increase in cardiovascular responses in the absence of direct physical contact with a different male mouse or animal handler.